2013
DOI: 10.1155/2013/714372
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Effects of Rabeprazole Sulfide on the Corrosion of Mild Steel in Acidic Chloride Solution

Abstract: The corrosion inhibition effect of Rabeprazole sulfide (RS) on mild steel in 1 M hydrochloric acid (HCl) was investigated using weight loss, potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), and chronoamperometric measurements. Protection efficiency of RS increases with the concentration and decreases with the rise in temperature. Adsorption of RS on mild steel surface in 1 M HCl follows Langmuir adsorption isotherm. The kinetic and thermodynamic parameters governing the adsorption pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…It was also discovered that the values of E ads increases with increase in the concentration of the inhibitor. The values of E ads and those of ∆H ads varies in a similar manner, and the average values of E ads − ∆H ads equal to 2.41 kJmol −1 , which is very close to the value of RT (2.51 kJmol −1 ) indicating that the adsorption process is unimolecular in nature [21].…”
Section: ) Thermodynamic Considerationssupporting
confidence: 67%
“…It was also discovered that the values of E ads increases with increase in the concentration of the inhibitor. The values of E ads and those of ∆H ads varies in a similar manner, and the average values of E ads − ∆H ads equal to 2.41 kJmol −1 , which is very close to the value of RT (2.51 kJmol −1 ) indicating that the adsorption process is unimolecular in nature [21].…”
Section: ) Thermodynamic Considerationssupporting
confidence: 67%
“…The correlation between dipole moment (µ) and inhibition efficiency of compounds is variously interpreted by several authors (Rajesh et al, 2018;Pavithra et al, 2013;Soltani et al, 2015). In fact some authors suggest that an increase in the dipole moment leads to a decrease in the inhibition efficiency.…”
Section: Figure 2 δE Evolution Per Inhibitormentioning
confidence: 99%
“…Furthermore, as most of the chemical compounds that prevent corrosion of metals and alloys are toxic, and thus pose a threat both to human health and environment, their usage is limited [9]. For this reason, several authors have reported the use of natural products, and drugs as green corrosion inhibitors for various metals and alloys viz: Ketoconazole [10], Tenofovir Disoproxil furmarate [11], Rabeprazole [12], Torsemide and Furosemide [13], Metol [14], Ciprofloxacin [15], Anthranilic acid [16],…”
Section: Introductionmentioning
confidence: 99%